PROFIL KOPERASI TIDAK AKTIF DI KECAMATAN DUMAI KOTA, KOTA DUMAI - Rahmadia, Nurul; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Cooperative is a type of business entity consisting of people or legal entity, based its activities based on the principle of people's economic movement based on the principle of kinship. The cooperative is a pillar of Indonesian economy, but in reality the cooperative has not been able to locate the position. Establishment of cooperatives is expected to improve the welfare of members but the visible inactive cooperatives more dominate than the growth of new cooperatives. In Dumai City the number of cooperatives of 273 units of 94 cooperatives is declared inactive and recommended for dissolution.This research was conducted in district Dumai City, Dumai City. The purpose of this study was to analyze the factors causing inactive cooperatives and to analyze the impact of inactive cooperatives on members of the cooperative. This study uses quantitative research methods, from the number of inactive cooperatives gained a population of 676 people. The sample of respondents in this study was determined based on Slovin formula of 87 people. The sampling technique using simple random sampling. Technique Data analysis is done by observation, interview and spread the questionnaire.The conclusion of the factors causing the cooperative is not active is the role of cooperative benefit is less felt for the members and the community because the cooperative has not been able to maximize the service and its business, the lack of cooperative management, the performance of the cooperative movers are still low, not RAT implementation as a form of responsibility of the board and supervisor, little capital, non-current business management. Inactive cooperatives have an impact on the congestion of cooperative enterprises, decreased co-operative income, collected capital and the disruption of social relationships among employees, officers and members. Keywords: Cooperative is not active, Cooperative Business and Work Ethic